The Chronic Disease Self-Management Program: A Resource for Use with Older CKD Patients - Washington, PhD, MSW, Tiffany; Hilliard, MPH, Tandrea; McGill, MD, Terrance (The Journal of Nephrology Social Work, 2013)
This commentary will briefly highlight the importance of promoting chronic disease self-management among older adults who are disproportionately affected by chronic kidney disease (CKD) stage 5. Older adults represent the fastest growing segment of the CKD stage 5 population. Undoubtedly, the rapidly aging population will present new challenges and demands for the CKD health care community. The Chronic Disease Self-Management Program (CDSMP) is one existing intervention that has been recognized as potentially having utility for use with the CKD population. In this paper, we highlight opportunities for expanding the CDSMP to the population of older adults undergoing hemodialysis. The CDSMP is a six-week, lay-led, evidence-based program that includes interactive activities, such as behavior specific action plans to improve chronic disease self-management behaviors. The CDSMP covers a wide range of health-related topics, including dealing with emotional struggles, effective communication, exercise, and nutrition. Special considerations for effective implementation of the CDSMP in hemodialysis settings are emphasized.